Plant Salinity Sensors: Current Understanding and Future Directions - Wang, Cheng-Feng; Han, Guo-Liang; Yang, Zong-Ran; Li, Yu-Xia; Wang, Bao-Shan (Frontiers in Plant Science, 2022)
Salt stress is a major limiting factor for plant growth and crop yield. High salinity causes osmotic stress followed by ionic stress, both of which disturb plant growth and metabolism. Understanding how plants perceive salt stress will help efforts to improve salt tolerance and ameliorate the effect of salt stress on crop growth. Various sensors and receptors in plants recognize osmotic and ionic stresses and initiate signal transduction and adaptation responses. In the past decade, much progress has been made in identifying the sensors involved in salt stress. Here, we review current knowledge of osmotic sensors and Na+ sensors and their signal transduction pathways, focusing on plant roots under salt stress. Based on bioinformatic analyses, we also discuss possible structures and mechanisms of the candidate sensors. With the rapid decline of arable land, studies on salt-stress sensors and receptors in plants are critical for the future of sustainable agriculture in saline soils. These studies also broadly inform our overall understanding of stress signaling in plants.